2003
DOI: 10.1086/344654
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Resistance: Origins, Epidemiology, and Impact

Abstract: The basic mechanisms of antibacterial resistance are well known, but critical new aspects continue to be discovered. Recently discovered factors with major implications for the emergence, dissemination, and maintenance of resistance include multidrug efflux, hypermutability, integrons, and plasmid addiction. Some resistances are widespread and others local, with prevalence rates often worst in newly prosperous countries and in those specialist units where antibacterial use is heaviest. Multidrug-resistant epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
293
0
44

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 478 publications
(342 citation statements)
references
References 92 publications
5
293
0
44
Order By: Relevance
“…This finding is also similar to those reported by others (15,16,19,20). Some scientists reported that presence of antibiotics in food of animals origin might hasten resistance development in humans.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is also similar to those reported by others (15,16,19,20). Some scientists reported that presence of antibiotics in food of animals origin might hasten resistance development in humans.…”
Section: Discussionsupporting
confidence: 92%
“…ESBLs are a major group of enzymes that confer resistance to several generations of β-lactam antibiotics, including third-generation cephalosporins [2,3]. ESBL-encoding genes that are primarily plasmidencoded include mostly TEM-, SHV-, and CTX-M-type enzymes [4]. Enterobacteriaceae, such as Klebsiella pneumoniae and Escherichia coli, are the main ESBL producers that have been reported globally.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial drug resistance is a rapidly increasing global problem ( 1 , 2 ), and prevalence varying widely among countries ( 3 ). Prevalence of resistance is positively correlated with prescribed outpatient drug use on a national level ( 4 , 5 ).…”
mentioning
confidence: 99%